The Three Dimensions of China Threat to Japan’s National Security - Leong, Le Chee; Md Akhir, Md Nasrudin (WILAYAH: The International Journal of East Asian Studies, 2014)
This paper provides a comprehensive outlook of the Japanese perception of China’s expansionist threats to Tokyo’s national security. In doing so, three dimensions of China threat, namely, Beijing’s military ascendancy, mounting Chinese civilian and maritime enforcement activities in the contended East China Sea, and mainland’s growing military influence over Taiwan, are examined in relations to Japan’s military, political and economic security in the region. The paper concludes that as far as the Japanese administration is concerned, China’s expansionism is a phenomenon that threatens Japan’s national security in a multi-dimensional way